Comparative Assessment of the Susceptibility of Multidrug-Resistant Clinical ESKAPE Bacterial Strains to the Biodegradation Products of MZZ-P and MZZ-MB Alloys - O.S. Movchan; B.A. Koteliukh; D.L. Kyryk (TERRA ORTHOPAEDICA, 2026)
Summary. Background. Antibiotic resistance of microorganisms belonging to the ESKAPE group is one of the leading threats to modern medicine, particularly in the context of implant-associated infections in orthopedics and traumatology. The search for new biomaterials with inherent antibacterial properties is a promising strategy for preventing such complications. Objective. To compare the antibacterial activity of the biodegradation products of MZZ-P and MZZ-MB alloys against multidrug-resistant clinical ESKAPE bacterial strains. Materials and Methods. The study was performed using multidrug-resistant strains of Staphylococcus aureus (MRSA), Enterococcus faecalis (VRE), Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Antibiotic susceptibility was determined according to EUCAST standards using the disk diffusion and serial dilution methods. The antimicrobial activity of alloy biodegradation products was assessed based on their bacteriostatic and bactericidal effects over a 72-hour incubation period, followed by subculturing on Mueller–Hinton agar. Statistical analysis was performed using the Wilcoxon test. Results. The biodegradation products of both alloys demonstrated pronounced antibacterial activity against all tested strains. A progressive decrease in the number of microbial colonies during incubation was observed, indicating a bactericidal effect. The MZZ-MB alloy demonstrated statistically significantly higher efficacy compared to MZZ-P (p < 0.05), particularly against Gram-negative non-fermenting bacteria. Conclusions. The biodegradation products of MZZ-P and MZZ-MB alloys exhibited strong bactericidal activity against multidrug-resistant ESKAPE pathogens. These findings support their potential use as biodegradable implants for the prevention of implant-associated infections.